1133-P: High Prediabetes Risk and Associated Risk Factors in Indian Population Based on Online Prediabetes Risk Test - VERMA, RITIKA; SAHAY, RAKESH; BANTWAL, GANAPATHI; KALRA, SANJAY; AGNIHOTRI, AKSHATA D.; TIWASKAR, MANGESH H.; ADE, SURESH F.; JUNEJA, ARCHANA M.; LAKHANI, OM J.; SINGAL, ARBINDER K. (Diabetes (New York, N.Y.), 2022)
Background: In India, a significant number of people are still diagnosed with diabetes at a later stage or after the complications have started. The unawareness about the disease and financial burden associated with the diagnostic testing remains a challenge. The study was aimed at the digital administration of a prediabetes risk test questionnaire to understand the people who are at high risk and more prone to developing prediabetes and eventually diabetes. Methods: A prediabetes risk questionnaire was developed based on the American Diabetes association risk score test. The test was completed by 1722 participants across India. The test was based on risk factors like age, gender, race, BMI, family history of diabetes, history of high blood pressure, and physical activity status. The scoring was done for three groups including high risk (score >5) , medium risk (score 3-5) , and low risk (score <3) . Binomial logistic regression was used for risk factor analysis among groups with low score and high-medium score. Results: The risk of prediabetes was low in 21 %, medium in 65 % and high in 12 % of participants. Out of all the participants 44 % had age ≥ 40 years, 71% were male, 96 % were asian, 74 % had BMI ≥ 23 kg/m2, 59 % of total participants have a family history of diabetes (first-degree relatives) , 17 % had high blood pressure, and 44 % were performing physical activity below recommended level of 150 mins per week. Among people with BMI ≥ 23 kg/m2, 89 % were having either high or medium risk scores. Among young people (age < 40 years) , 67 % were having high or medium scores. The odds ratio for score in high or medium range for people with BMI ≥ 23 kg/m2 and age ≥ 40 years was 38.51 (95% CI: 24.19-61.30, P<0.001) and 78.89 (95% CI: 41.21-136.06, P<0.001) respectively. Conclusion: The study showed that out of all the participants, 77% had a high or medium risk score. The study highlights the importance of using a prediabetes risk calculator as a tool for improving awareness about the risk of developing prediabetes.